Antibacterial Activity Test of Breadfulness Leaf Extract Plaster Preparation ( Artocarpus altilis ) In Vitro and In Vivo In The Treatment of Mice Cut Wounds - Simorangkir, Delisma Marsauli (JURNAL BIOSAINS, 2025)
The skin is the largest organ in the human body. One of the problems that often occurs in the skin is wounds. Wounds are damage or loss of tissue in the body caused by a factor, one type of wound is a cut wound. Cuts occur due to friction with objects causing linear tears in the skin and underlying tissue. Cuts can cause infections due to bacteria. Breadfruit leaves (Artocarpus altilis) contain flavonoid compounds that can regenerate the skin by increasing collagen in the skin and have bactericidal properties. This study aims to determine the optimal concentration in the activity of breadfruit leaf extract formulated in the form of plasters against in vitro and in vivo tests in the treatment of cut wounds in mice. This study used the maceration method in making the extract using 96% ethanol solvent. Breadfruit leaf extract was formulated into a plaster preparation with various concentrations F1: EEDS 10%, F2: EEDS 15%, F3: EEDS 20%, and F4: EEDS 25%. The plaster preparation was evaluated to determine the physical properties and compounds of the wound dressing material by conducting thickness tests, humidity tests, pH tests, organoleptic tests, FTIR tests, activity tests of the preparation against in vitro tests and in vivo tests. The results showed that the concentration of EEDS 25% with a value of 24.35 against the in vitro test using Staphylococcus aureus bacteria with a Hansaplast plaster comparator with a value of 16.35. In the in vitro test in the treatment of mouse cuts, it was stated that the concentration of EEDS 25% with a healing day of 10.6 days was close to the healing day of the Hansaplast plaster comparator with a healing day of 9.3 days.